UPAYA MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING KELAS V SDN UNGGULAN I PULAU MOROTAI - Sibua, Abd Sarman; Ningsih, Kikik Ayu (STKIP Pesisir Selatan, 2024)
This research aims to increase student creativity and learning outcomes using the Project Based Learning Model for Class VB SDN Unggulan I Morotai Island. This research uses a classroom action research approach. The data collected in this research is descriptive, namely describing each stage (cycle) carried out. The research results show that the use of the Project Based Learning model for class VB students at SDN Unggulan I Morotai Island can increase student creativity and learning outcomes. The research results showed that students experienced increased creativity and learning outcomes using the Project Based Learning learning model that was applied. In cycle I, it is known that there were 13 students (44.82%) who were declared complete, while the remaining 16 students (55.17%) had not yet achieved completeness out of a total of 29 students. However, in cycle II there was an increase in scores above the average (>70) or it was known that 26 students (89.65%) were declared complete, while it was known that the number of students who had not achieved completeness was 3 students (10.34%) out of a total of 29 student.